APLIKASI WEBCAM UNTUK SISTEM PEMANTAUAN RUANG BERBASIS WEB - Kartika Firdausy; Selamat Riyadi; Tole Sutikno; Muchlas Muchlas (Universitas Ahmad Dahlan, 2008)
A security has become very important along with the increasing number of crime cases. If some security system fails, there is a need for a mechanism that capable in recording the criminal act. Therefore, it can be used for investigation purpose of the authorities. The objective of this research is to develop a security system using video streaming that able to monitor in real-time manner, display movies in a browser, and record a video as triggered by a sensor. This monitoring system comprises of two security level camera as a video recorder of special events based on infrared sensor that is connected to a microcontroller via serial communication and camera as a real-time room monitor. The hardware system consists of infrared sensor circuit to detect special events that is serially communicated to an AT89S51 microcontroller that controls the system to perform recording process, and the software system consists of a server that displaying video streaming in a webpage and a video recorder. The software for video recording and server camera uses Visual Basic 6.0 and for video streaming uses PHP 5.1.6. As the result, the system can be used to record special events that it is wanted, and can displayed video streaming in a webpage using LAN infrastructure.